1981
DOI: 10.3133/pp529n
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic continental shelf and slope of the United States: Macrobenthic invertebrate fauna of the middle Atlantic bight region — Faunal composition and quantitative distribution

Abstract: Areas of several bathymetric zones within each subarea and total area of Middle Atlantic Bight region __ 5 Quantitative taxonomic composition of the macrobenthic invertebrate fauna, in both number of individuals and biomass, representing the entire Middle Atlantic Bight region

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…For example, energy budgets have been postulated for western North Atlantic regions on the basis of a general macrofauna biomass-conversion of 0.6 Kcal (2.S KJ/g) wet weight (Mills and Fournier, 1979;Walsh, 1981). With the use of results of the extensive benthic study of the Middle Atlantic by Wigley and Theroux (1981), conversion of the biomass composition of the major taxa (71°/0 molluscs, 12°/0 echinoderms, 7°1o polychaetes, SOlo crustaceans, and SOlo others) to energy from the data in Table 1 yields an average value of about 3.2 KJ/g wet weight or about 0.8 Kcal, a 30°/0 increase. This value may still be conservative because it is based on an 83°/0 contribution of molluscs (99°/0 shelled) and echino- Cummins and Wuycheck (1971).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, energy budgets have been postulated for western North Atlantic regions on the basis of a general macrofauna biomass-conversion of 0.6 Kcal (2.S KJ/g) wet weight (Mills and Fournier, 1979;Walsh, 1981). With the use of results of the extensive benthic study of the Middle Atlantic by Wigley and Theroux (1981), conversion of the biomass composition of the major taxa (71°/0 molluscs, 12°/0 echinoderms, 7°1o polychaetes, SOlo crustaceans, and SOlo others) to energy from the data in Table 1 yields an average value of about 3.2 KJ/g wet weight or about 0.8 Kcal, a 30°/0 increase. This value may still be conservative because it is based on an 83°/0 contribution of molluscs (99°/0 shelled) and echino- Cummins and Wuycheck (1971).…”
Section: Resultsmentioning
confidence: 99%
“…Species were selected for analysis on the basis of their relative contribution to energy pools and budgets of the shelf, i.e. they comprise significant standing stocks (Wigley and Theroux, ;1981), or because they are food for many fishery resource species (Edwards and Bowman, 1979). For each species, the most common sizes of animals in the collections or in the stomachs of predators were selected for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Samples ( Fig. 1) were taken in the MidAtlantic Bight area, a portion of the eastern North American continental shelf, between 36°30' and 41°N, and 71°30' and 74°50' W, in depths between 27 and 104 m. This area has temperate water temperatures (Table 1) and sandy sediments often mixed with shells, with occasional patches of sandy gravel and sandy silt (Boesch 1979, Wigley & Theroux 1981. Samples taken from a more northeasterly region (Georges Bank and vicinity), between 40°24' and 42°10' N, and 66°25' and 69°50' W, were used for comparative purposes.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of daytime beam trawl sampling may have influenced our results because some species have been found to exhibit diel patterns of microhabitat use on the northeast U.S. shelf (Diaz et al, 2003); consequently additional roundthe-clock sampling may lead to the discovery of different habitat relationships than those we report here. Nevertheless, taxon-specific relationships with habitat on the shelf have previously been shown for fish and macro-invertebrates and were most closely associated with sediment characteristics (Wigely and Theroux, 1981;Theroux and Wigely, 1998;Methratta andLink, 2006, 2007), depth (in both the cross-shelf and shoal formations) (Viscido et al, 1997;Steves et al, 1999;Methratta and Link, 2007;Vasslides and Able, 2008;Slacum et al, 2010), and bottom water temperature, particularly with seasonal temperature changes (Steves et al, 1999;Malek et al, 2014). Hale (2010), in examining estuarine and near shore sample locations, also showed that salinity was related to macro-invertebrate assemblages.…”
Section: Cca1 (182%)mentioning
confidence: 79%
“…3). Regional variation in assemblage structure on the northeast U.S. shelf, following a south to north gradient, has been described for both fish (Gabriel, 1992;Lucey and Nye, 2010) and macro-invertebrates (Wigely and Theroux, 1981;Theroux and Wigely, 1998;Hale, 2010). Consequently, impacts of WEAs spread along the shelf may become additive for assemblages that span large distances (i.e., 50-100 km).…”
Section: Cca1 (182%)mentioning
confidence: 99%